Digital Transformation of Production Study: An Efficiency Analysis of GI-PS System Implementation Using a Mixed Methods Approach in the Garment Industry - Saifurohman; Lukman Hidayat; Wine Regyandhea Putri (Universitas Insan Cendekia Mandiri, 2026)
The efficiency of data management in garment production plays a critical role in supporting timely decision-making and improving overall productivity. One of the main challenges faced by garment industries is the delay in submitting production study data caused by manual data processing systems. This study aims to analyze the effect of implementing the Globalindo Intimates Production study (GI-PS) system on the speed of production study data submission at PT Globalindo Intimates. This research employed a mixed methods approach, combining quantitative and qualitative methods. Quantitative data were collected by measuring the time required to submit production study data before and after the implementation of the GI-PS system, while qualitative data were obtained through interviews with industrial engineering staff and management. The quantitative analysis used a paired sample t-test to examine differences in data submission time. The results show a significant reduction in data submission time after the implementation of the GI-PS system, indicating that the digital-based system effectively improves efficiency and accuracy in production data management. Qualitative findings further support that the system enhances workflow, reduces administrative workload, and improves coordination among departments. Therefore, the GI-PS system can be considered an effective solution to improve production study data management in the garment industry. Practically, the implementation of digital systems such as GI-PS can serve as a solution for garment companies to accelerate the flow of production information, improve the accuracy of operational decision-making, and support increased efficiency and competitiveness in an increasingly dynamic industrial environment.